2021
DOI: 10.5468/ogs.20205
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D and calcium in the relief of primary dysmenorrhea: a systematic review

Abstract: Dysmenorrhea is one of the well-established problems among women of reproductive age and can have adverse effects on the quality of life of the individual. Some studies suggest a relationship between vitamin D (Vit D) and calcium deficiency and the emergence of early dysmenorrhea. Accordingly, a systematic study was performed to investigate the role of calcium and Vit D in the relief of primary dysmenorrhea. A systematic literature search was performed in PubMed, Web of Science, Scopus, Science Direct, and Goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
0
32
0
4
Order By: Relevance
“…There are several reports indicating an inverse relationship between vitamin D (Vit D) status and risk of depressive symptoms [ 7 , 8 ], fibromyalgia [ 9 ], and uterine leiomyomas [ 10 ]. Additionally, low levels of Vit D and calcium can promote dysmenorrhea pain by elevating prostaglandin genesis or decreasing intestinal calcium absorption [ 11 ]. Moreover, a high Vit D intake may mitigate the risk of PMS, by effects on sex steroid hormone and neurotransmitter activities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports indicating an inverse relationship between vitamin D (Vit D) status and risk of depressive symptoms [ 7 , 8 ], fibromyalgia [ 9 ], and uterine leiomyomas [ 10 ]. Additionally, low levels of Vit D and calcium can promote dysmenorrhea pain by elevating prostaglandin genesis or decreasing intestinal calcium absorption [ 11 ]. Moreover, a high Vit D intake may mitigate the risk of PMS, by effects on sex steroid hormone and neurotransmitter activities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review reported an inverse relation between serum vitamin D/calcium and severity of PD, and reduced severity of PD after vitamin D/calcium intake [12].…”
Section: Discussionmentioning
confidence: 99%
“…Low serum vitamin D was reported during the luteal phase of the menstrual cycle [11], and a systematic review reported vitamin D de ciency in severe PD [12].…”
Section: Introductionmentioning
confidence: 99%
“…It could be assumed that vitamin D and parathyroid hormone play a role in the intensity of systemic physical and mental symptoms of premenstrual syndrome [ 40 ]. Moreover, taking calcium and vitamin D supplements will improve the physical and psychological symptoms of premenstrual syndrome and primary dysmenorrhea [ 16 , 17 ]. We did not measure the calcium level in this study, and its role in the development of symptoms and responses to vitamin D supplementation in patients with primary dysmenorrhea warrants further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the serum levels of vitamin D reduce in the luteal phase of the menstrual cycle [ 16 ]. The role of vitamin D deficiency in inducing or exacerbating the symptoms of primary dysmenorrhea has been addressed by some studies [ 17 ]. Vitamin D metabolites (e.g., 25[OH]D and 1,25[OH]2D) reduce the levels of inflammatory cytokines and associated contractile factors (prostaglandin) in the endometrium and incapacitate its biological activity by affecting its receptors in the endometrium [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%